Metacognition, calibration, and self-regulated learning: an exploratory study of undergraduates in a business school. (2nd January 2019) - Stoten, David William
ABSTRACT: Self-regulated learning (SRL) is a fertile ground for research into learning in higher education. Until now, the dominant research methodology has concentrated on quantitative analyses of separate components within the Zimmerman model with the aim of isolating possible factors in learning trajectories and evaluating their relative importance in the process of learning. Recent approaches to SRL research have sought not only to measure students' progress, but also to investigate how interventions may generate a positive impact on learning from a qualitative perspective. This research adopted a qualitative approach, and so contributes to the creation of new avenues for SRL research. The research, conducted over two years in a business school at a post-1992 university, involved students enrolled on undergraduate degree in an evaluation of learning diary as a learning aid. The findings suggest that learning diaries may provide scaffolding support for students, especially those who lack confidence.